Assessing the Role of Technology Adoption in China's Growth Performance - Nadja Wirz (University of Copenhagen, Economic Policy Research Unit (EPRU), 2008)
China has experienced a period of tremendous economic growth in recent years. In an attempt to explain this development, several existing growth-accounting studies reveal that impressively high rates of productivity growth have been at the heart of China's performance. This study investigates to what extent these productivity increases can be explained by technology-adoption theory. In less developed countries, the key element behind technological progress is technology adoption, the process of copying technological knowledge invented throughout the world. To uncover a measure of China's technological advances, the paper constructs a hybrid of some prominent technology-adoption models and calibrates it to reasonable parameter values. The calibrated version of the model is then combined with Chinese economic data. For the period 1978-2005, the analysis finds that the Chinese performance can be explained to a surprisingly large extent by the suggested technology-adoption framework. It can account for roughly 80% of China's productivity gains.
Keywords: O11; O30; O40; O52; 330; technological progress; technology adoption; TFP; China; Technischer Fortschritt; Technologiewahl; Innovationsdiffusion; Produktivität; China